Inhibiting NLRP3 inflammasome attenuates apoptosis in contrast-induced acute kidney injury through the upregulation of HIF1A and BNIP3-mediated mitophagy. Issue 10 (3rd October 2021) - Lin, Qisheng; Li, Shu; Jiang, Na; Jin, Haijiao; Shao, Xinghua; Zhu, Xuying; Wu, Jingkui; Zhang, Minfang; Zhang, Zhen; Shen, Jianxiao; Zhou, Wenyan; Gu, Leyi; et al.
ABSTRACT: The pathogenetic mechanism of contrast-induced acute kidney injury (CI-AKI), which is the third most common cause of hospital-acquired AKI, has not been elucidated. Previously, we demonstrated that renal injury and cell apoptosis were attenuated in nlrp3 knockout CI-AKI mice. Here, we investigated the mechanism underlying NLRP3 inhibition-mediated attenuation of apoptosis in CI-AKI. The RNA sequencing analysis of renal cortex revealed that the nlrp3 or casp1 knockout CI-AKI mice exhibited upregulated cellular response to hypoxia, mitochondrial oxidation, and autophagy when compared with the wild-type (WT) CI-AKI mice, which indicated that NLRP3 inflammasome inhibition resulted in the upregulation of hypoxia signaling pathway and mitophagy. The nlrp3 or casp1 knockout CI-AKI mice and iohexol-treated HK-2 cells with MCC950 pretreatment exhibited upregulated levels of HIF1A, BECN1, BNIP3, and LC3B-II, as well as enhanced colocalization of LC3B with BNIP3 and mitochondria, and colocalization of mitochondria with lysosomes. Additionally, roxadustat, a HIF prolyl-hydroxylase inhibitor, protected the renal tubular epithelial cells against iohexol-induced injury through stabilization of HIF1A and activation of downstream BNIP3-mediated mitophagy in vivo and in vitro . Moreover, BNIP3 deficiency markedly decreased mitophagy, and also significantly exacerbated apoptosis and renal injury. This suggested the protective function of BNIP3-mediated mitophagy in CI-AKI. This study elucidated a novel mechanism in which NLRP3 inflammasome inhibition attenuated apoptosis and upregulated HIF1A and BNIP3-mediated mitophagy in CI-AKI. Additionally, this study demonstrated the potential applications of MCC950 and roxadustat in clinical CI-AKI treatment. Abbreviations: BNIP3: BCL2/adenovirus E1B interacting protein 3; Ctrl: control; DAPI: 4′, 6-diamidino-2-phenylindole dihydrochloride; EGLN2/PHD1: egl-9 family hypoxia-inducible factor 2; HIF1A: hypoxia inducible factor 1, alpha subunit; H-E: hematoxylin and eosin; IL18: interleukin 18; IL1B: interleukin 1 beta; LAMP1: lysosomal-associated membrane protein 1; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; mRNA: messenger RNA; NFKB/NF-κB: nuclear factor of kappa light polypeptide gene enhancer in B cells; NLRP3: NLR family, pyrin domain containing 3; NS: normal saline; PRKN/Parkin: parkin RBR E3 ubiquitin protein ligase; PINK1: PTEN induced putative kinase 1; RNA: ribonucleic acid; SEM: standard error of the mean; siRNA: small interfering RNA; TEM: transmission electron microscopy; TUBA/α-tubulin: tubulin, alpha; TUNEL: terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling; VDAC: voltage-dependent anion channel; WT: wild-type